Targeted senolytic delivery system to treat liver cirrhosis - Pitrez, João Pedro Oliveira Santos (2024)
Aging can be defined as a detrimental process, leading to a decline of function in tissues and organs. At a biological level, aging results from the impact of the accumulation of a wide variety of molecular and cellular damage over time. Cellular senescence is a physiological response to endogenous and/or exogenous stress, described by a stable cell-cycle arrest, where cells stop replicating but remain metabolically active, upregulation of pro-survival pathways, and secretion of a sophisticated phenotype. With aging there is an accumulation of senescent cells in various tissues and organs. One organ profoundly affected by the accumulation of senescent cells is the liver, as observed in several in vivo studies, which noted a higher accumulation of senescent cells. Although senescence affects all types of cells that make up the liver, we will focus our strategy on endothelial cells. Liver endothelial cells, named, liver sinusoidal endothelial cells (LSECs) are specialized endothelial cells, due to their distinctive morphology and functions. LSECs are indispensable in liver physiology, immunology, and pathophysiology, so a dysfunction of these cells can have a meaningful impact in liver homeostasis. LSECs dysfunction is responsible or can aggravate several liver disorders, such as liver fibrosis, cirrhosis, and even hepatic cancer, which makes LSECs a therapeutic target. Clearance of senescent cells has already been demonstrated to be an effective ameliorator of senescence effects in various in vitro and in vivo models, and there is one class of pharmacological agents mostly responsible for this clearance. This class of small molecules is capable of effectively eliminating senescent cells by acting on the pro-survival pathways of these cells. One senolytic in particular, Navitoclax (Nav), has shown high senolytic effects in several preclinical studies. However, Nav, as well as other senolytics, present associated toxicities, so an effective targeted delivery system is needed to exclusively kill senescent cells. In this work, a nanoformulation was tested for the encapsulation of Nav to reduce the side effects of the senolytic and selectively eliminate senescent LSECs. The bioactivity of the nanoformulation was tested in healthy LSECs and senescent LSECs, induced by gamma radiation, and the senescence program was characterized. Nav-loaded NPs selectively induced cell death in senescent LSECs, only affecting healthy LSECs in extreme concentrations of NPs, and presented a higher senolytic index than soluble Nav. This targeted drug delivery system thus demonstrates capable of effectively targeting senescent LSECs, eliminating the side-effect toxicity of Nav, representing a promising therapeutic treatment of age-related liver diseases.